Ankle Blood Pressure and Pulse Pressure as Predictors of Cerebrovascular Morbidity and Mortality in a Prospective Follow-Up Study - Heikki J. Hietanen; Rauni Pääkkönen; Veikko Salomaa (Stroke Research and Treatment)
Background and Objective. We examined the association of elevated ankle blood pressure (ABP), together with exercise blood pressure, with incident cerebrovascular (CV) morbidity and mortality in a prospective follow-up study of 3,808 patients. The results were compared with pulse pressure, another indicator of arterial stiffness. Methods. Patients with normal ankle and exercise brachial blood pressures were taken as the reference group. Pulse pressure was considered as quartiles with the lowest quartile as the reference category. Results. A total of 170 subjects had a CV event during the follow-up. Multivariate adjusted hazard ratio of a CV event was 2.24 (95% CI 1.43–3.52, 𝑃<.0001) in patients with abnormal ABP. The pulse pressure was significant only in the model adjusted for age and sex. Conclusion. The risk of a future CV event was elevated already in those patients among whom elevated ABP was the only abnormal finding. As a risk marker, ABP is superior to the pulse pressure.